Social Escape or Concealment of Sins? The Communication Corruption Analysis of the Secondary Social Media Account Use - Nasution, Asri Annisa; Wijaya, Bambang Sukma (Journal Communication Spectrum: Capturing New Perspectives in Communication, 2023)
The overuse of social media has given rise to having secondary accounts on one platform. Various studies have found motives for double accounts, especially on Instagram, such as identity disguise, personal use, creative expression, and privacy. More-login can help manage multiple accounts while maintaining anonymity and security, making it easier for users to explore various aspects of their online presence. Fake Instagram accounts (often called ‘finsta’) are also widespread. Apart from personal motives, there are also ‘professional’. Motives that lead to crime. This article highlights the use of multiple accounts in the context of communication corruption by dissecting aspects of corrupt messages, media misuse, context exploitation, and corrupt behaviour. A case study approach by analysing two participants secondary accounts in depth, accompanied by interviews, digital observations,and document searches, indicates that message corruption occurs in the form of content manipulation, both visual and verbal, concealment of facts, and euphemisms for evil—media corruption by impersonating social media accounts and using media to inflate one’s meaning. Context corruption occurs in inauthentic impression management and misleading public views toward a particular self- picture. Corrupt behaviour is indicated by intentions, motives, and obsession with concealing self-facts and constructing a false social image. The practice of multiple accounts implies that users not only have a ‘other world’ that is free, authentic, and sometimes anti-mainstream but also an image and life imprisoned by the social eye on the other side. So, the second account can be called a social escape room. This research is novel because it first examines the second account phenomenon from the perspective of communication corruption theory with its various consequences. To cite this article (7th APA style): Nasution, A. A. & Wijaya, B. S. (2023). Social escape or concealment of sins? The communication corruption: Analysis of the secondary social media account use. Journal Communication Spectrum: Capturing New Perspectives in Communication 13(2), 106-114. http://dx.doi.org/10.36782/jcs.v13i2.2100